The Role of Financial Inclusion to Enhance Social Progress in Developed and Developing Countries - Shahid, Sara; Asghar, Nabila (Pakistan Journal of Humanities and Social Sciences, 2024)
This study examines the role of financial inclusion in enhancing the social progress of developed and developing economies. Social progress is a key indicator of a country's development. It captures a range of factors that shape the well-being of the economy. Therefore, financial inclusion promotes social progress through financial resources. This study uses a sample of 32 developed and 18 developing countries from 2000 to 2023. The econometric approach Panel Quantile Autoregressive Distributed Lag (PQARDL) model is used to investigate the short and long-term impact among the variables. The results of the study show that financial inclusion and strong institutions positively impact Social Progress (SP) in developed countries while industrialization, population growth and transportation has negative impact on it. On the contrary, in developing countries, financial inclusion, institutions, population growth, and industrialization have a positive impact on SP while transportation harms it. The study suggests that developing countries need to promote financial literacy, strengthen governance, support green industrialization, improve sustainable transport, and control high population growth. While, developed economies should focus on financial product diversification, policy reform in healthcare and education, promote sustainable practices, and managing demographic changes.